2021
DOI: 10.5585/gep.v12i2.20121
|View full text |Cite
|
Sign up to set email alerts
|

Valor e projetos: a contribuição da perspectiva de marketing

Abstract: A gestão de projetos vem passando por profundas transformações ao longo dos últimos anos. Dentre estas mudanças, tem se observado uma maior permeabilidade a outras áreas do conhecimento. Isto é bastante saudável na medida em que permite que novas ou complementares abordagens em gestão de projetos possam ser incorporadas aos métodos tradicionais, ampliando assim as possibilidades de resultado de um projeto. Neste contexto, a tradicional visão de que os projetos devem ter preocupação com escopo, custo e prazo nã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 13 publications
0
3
0
6
Order By: Relevance
“…For a project-based organization (PBO), projects mean income, and for a project supported organizations (PSO) they are expenses (Lundin, 2016). Also, recent studies confirmed that, no matter which project management approach used, we are moving from planning-oriented practices to a more systemic approach oriented towards value delivery (Bizarrias, Penha, & Silva, 2021) Based in this discussion, this study is based in a triple construct fundamental. First of all are the sustainability studies, including sustainability management theories, specifically the "by" and "of" sustainability projects typology.…”
Section: ____________________________________________________________...mentioning
confidence: 83%
“…For a project-based organization (PBO), projects mean income, and for a project supported organizations (PSO) they are expenses (Lundin, 2016). Also, recent studies confirmed that, no matter which project management approach used, we are moving from planning-oriented practices to a more systemic approach oriented towards value delivery (Bizarrias, Penha, & Silva, 2021) Based in this discussion, this study is based in a triple construct fundamental. First of all are the sustainability studies, including sustainability management theories, specifically the "by" and "of" sustainability projects typology.…”
Section: ____________________________________________________________...mentioning
confidence: 83%
“…Uma outra perspectiva de valor é o percebido pelo cliente do projeto, o qual direciona a estratégia empresarial e envida seus esforços para entregar valor para o cliente em uma perspectiva iterativa e colaborativa (Bizarrias, Penha, & Silva, 2021).…”
Section: Gestão De Benefícios Em Gestão De Projetosunclassified
“…The management of projects has been increasing as a practice for organisations facing difficult business challenges and has evolved from product focus to value focus for its project stakeholders (Obradović et al , 2016; Winter and Szczepanek, 2008). Value management has become an essential tool for companies (Garti and Dolan, 2019) and is a deeply rooted concept from the consumer perspective that evolved separately from project management (Voss and Kock, 2013; Kumar et al , 2011; Bizarrias et al , 2020; Bizarrias et al , 2021). But it has become increasingly closer to project management which underpins its conceptual and theoretical contribution.…”
Section: Introductionmentioning
confidence: 99%